Is effective mass in combat sports punching above its weight? - Lenetsky, S.; Nates, R. J.; Brughelli, M.; Harris, N. K. (Human Movement Science, 2015)
The segmental and muscular complexity of the human body can result in challenges when examining the kinetics of impacts. To better understand this complexity, combat sports literature has selected effective mass as a measure of an athlete`s inertial contribution to the momentum transfer during the impact of strikes. This measure helps to clarify the analysis of striking kinetics in combat sports. This paper will review: (1) effective mass as a concept and its usage as a measure of impact intensity in combat sports, (2) the neuromuscular pattern known as "double peak muscle activation" which has been theorized to help enhance initial hand velocity upon impact and joint stiffening during impact, (3) the methods and equations used to calculate effective mass, and (4) practitioner recommendations based on the literature. We will argue in this manuscript that the act of punching presents unique challenges to the current understanding of effective mass due to additional force application during impact. This review will improve the understanding of effective mass and its roles in effective striking serving to underpin future research into performance enhancement in striking based combat sports.